Adaptasi Dakwah dalam Tradisi Tolak Bala Masyarakat Kota Parepare (Adaptation of Da'wah in the Tradition of Tolak Bala in the Community of Parepare City) - Nurhikmah Nurhikmah; Nurhidayat Muhammad Said; Abdul Malik; Muhammad Taufiq Syam (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Tolak bala is a religious tradition of the people of Parepare City which is still practiced in several mosques and aims to keep themselves and their families away from all disasters. Tradition that describes a form of religious and cultural adaptation in society. This study tries to describe the form and process of adaptation of da'wah in the implementation of the tradition of rejecting reinforcements which shows the modification of Islamic values on the subject, procession and representation of symbols through the theory of cultural adaptation. This study uses a qualitative descriptive method with a phenomenological approach to describe various conditions and social phenomena that occur in the people of Parepare City. Data were collected through the process of observation, interviews and documentation. The results of this study indicate a modification of Islamic values in the implementation of the tradition of tolak bala carried out by the people of Parepare City. This modification shows that the adaptation of the concept of da'wah bil hal in the intercorrelation of Islam and local culture is not contradictory, but complementary. This harmonization facilitates the transformation of da'wah values in society.